2012
DOI: 10.1270/jsbbs.62.46
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of <i>MdACS3</i> null alleles in apple (<i>Malus</i> × <i>domestica</i> Borkh.) and its relevance to the fruit ripening characters

Abstract: Expression of MdACS3a , one of the ripening-related ACC synthase genes, plays a pivotal role in initiating the burst of ethylene production by MdACS1 in apple fruit. Although previous studies have demonstrated the presence of MdACS3a -null alleles through deficiency of transcription activity or loss of enzyme activity due to amino acid substitution, which may affect the storage properties of certain fruit cultivars, an overall picture of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…In the present study, a QTL showing significant correlation with harvest time was found at the top of LG Tai15 near the PPACS2 locus. Kunihisa et al (2014) reported that two ACC synthase genes MdACS1 ( Harada et al 2000 ) and MdACS3 ( Bai et al 2012 ) were mapped in LG 15 in apple and that the harvest time QTL at the bottom of LG 15 around MdACS1 was tightly linked to preharvest fruit drop in apple. We suggest that ACC synthase genes ( PPACS2 , MdACS1 ) have multiple functions affecting harvest time, preharvest fruit drop and fruit storage potential both in Japanese pear and in apple.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a QTL showing significant correlation with harvest time was found at the top of LG Tai15 near the PPACS2 locus. Kunihisa et al (2014) reported that two ACC synthase genes MdACS1 ( Harada et al 2000 ) and MdACS3 ( Bai et al 2012 ) were mapped in LG 15 in apple and that the harvest time QTL at the bottom of LG 15 around MdACS1 was tightly linked to preharvest fruit drop in apple. We suggest that ACC synthase genes ( PPACS2 , MdACS1 ) have multiple functions affecting harvest time, preharvest fruit drop and fruit storage potential both in Japanese pear and in apple.…”
Section: Discussionmentioning
confidence: 99%
“…The higher ethylene and respiration in “Anna” was accompanied by higher expression of major ethylene biosynthesis genes, MdACSO2, 4 , and 7 and particularly MdACS3a during early fruit development. It has been reported that the cultivars’ specific expression of MdACS3a , and existence of specific allele of this gene leads to high ethylene production in different apple cultivars ( Wiersma et al, 2007 ; Wang et al, 2009 ; Varanasi et al, 2011 ; Bai et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“… 18 In a previous study, the two null alleles MdACS3a-G289V ( CAPS 866 T ) and Mdacs3a ( CAPS 870 T ) were concluded to affect the ripening initiation only in late-season apple cultivars, but not in early- or mid-season ones. 20 Such discrepancy in different studies regarding the roles of the two null alleles of MdACS3a , particularly MdACS3a-G289V , calls for further investigations into the role of MdACS3a-G289V . Nevertheless, alleles MdACS1–2 and Mdacs3a ( CAPS 870 T ) are clearly demonstrated to be beneficial for breeding apples of low or delayed ethylene profiles in this study, a first effort that simultaneously assessed the roles of MdACS1 and MdACS3a in fruit ethylene production and softening in highly diverse Malus materials.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent report, however, the allelotypes of MdACS3a were demonstrated to affect the ripening initiation of late-maturing cultivars only, but not the early- or mid-maturing cultivars. 20 To better assess the roles of MdACS1 and MdACS3a , two approaches were taken in this study. The first approach was to estimate the allelotypic effect of the two genes by evaluating fruit ethylene production levels and softening rates in 97 diverse Malus accessions and 34 progeny from 2 controlled crosses.…”
Section: Introductionmentioning
confidence: 99%